Oligotrophication and Metabolic Slowing-Down of a NW Mediterranean Coastal Ecosystem - Agusti, Susana; Martinez-Ayala, Juan; Regaudie-de-Gioux, Aurore; Duarte, Carlos M. (Frontiers in Marine Science, 2017)
Increased oligotrophication is expected for oligotrophic areas as a consequence of ocean warming, which reduces diffusive vertical nutrient supply due to strengthened stratification. Evidence of ocean oligotrophication has been, thus far, reported for the open ocean. Here we reported oligotrophication and associated changes in plankton community metabolism with warming in a pristine, oligotrophic Mediterranean coastal area (Cap Salines, Mallorca Island, Spain) during a 10 years time series. As a temperate area, there were seasonal patterns associated to changes in the broad temperature range (12.0–28.4°C), with a primary phytoplankton bloom in late winter and a secondary one in the fall. Community respiration (R) rates peaked during summers and showed higher rates relative to gross primary production (GPP) with a prevalence of heterotrophic metabolism (2/3's of net community production (NCP) estimates). Chlorophyll a concentration significantly decreased with increasing water temperature in the coastal site at a rate of 0.014 ± 0.003 μg Chla L−1 °C−1 (P < 0.0001). The study revealed a significant decrease with time in Chlorophyll a concentration and nutrients concentration, indicating oligotrophication during the last decade. Community productivity consistently decreased with time as both GPP and R showed a significant decline. Warming of the Mediterranean Sea is expected to increase plankton metabolic rates, but the results indicated that the associated oligotrophication must lead to a slowing down of the community metabolism.